Psychosocial factors and mental illness among employees in private development companies in Malaysia / Mohd Zulkifli Abdullah... [et al.] - Abdullah, Mohd Zulkifli; Othman, Abdul Kadir; Solat, Naliza; Saidon, Sharmila (Universiti Teknologi Mara Cawangan Kelantan, 2020)
Employee productivity has become the primary concern among many companies, irrespective of public or private companies. One of the determinants of productivity is mental illness (having negative thoughts or feelings most of the time) since employees had mental illness are having difficulties in working effectively. Mental illness is a common disease that affects a person's thinking, emotion, behaviour and also causes functional impairment. Employees working in private development companies are not excluded from experiencing the problem of mental illness. Therefore, this study is meant to investigate whether psychosocial factors (decision latitude, social support and working environment) contribute to mental illness among the employees. Furthermore, this study is also meant to examine the moderating effect of emotional distress on the relationship between psychosocial factors and mental illness. Using 216 responses from employees working in private development companies, the results of multiple regression analysis show that only decision latitude significantly contributes to explaining mental illness among employees in private development companies. On the other hand, emotional distress does not significantly moderate the relationship between psychosocial factors and mental illness, indicating that emotional distress does not play a significant role in affecting the connection between psychosocial factors and mental illness. The findings of the study suggest that employees should be provided with sufficient decision latitude (freedom to make decisions) so that they will not experience mental illness. As a consequence, they will work hard to increase the productivity of the company in general. Implications for future study are also discussed in the paper